Acute Disseminated Melioidosis Presenting with Septic Arthritis and Diffuse Pulmonary Consolidation in an Otherwise Healthy Adult: A Case Report - Hai Sherng Lee; Abdul Azeez Ahamed Riyaaz; Seng Hong Yeoh (International Journal of Medical Students, 2015)
Background: Melioidosis is an infectious disease caused by Burkholderia pseudomallei. It is most prevalent in South-East Asia, northern Australia, and the Indian subcontinent. Septic arthritis is a rare manifestation of melioidosis. Melioidosis is usually found in patients with diabetes, heavy alcohol use, or chronic lung disease.